2018
DOI: 10.1002/biot.201700746
|View full text |Cite
|
Sign up to set email alerts
|

High Intracellular Seed Train BiP Levels Correlate With Poor Production Culture Performance in CHO Cells

Abstract: Consistent cell culture performance is a prerequisite to ensure product quality consistency and achieve productivity goals for the manufacture of recombinant protein therapeutics, including monoclonal antibodies. Here a peculiar observation is reported where high levels of intracellular BiP in seed train cultures are consistently predictive of poor cell culture performance in the subsequent inoculum and production cultures for a monoclonal antibody produced in CHO cells. This investigation suggests that in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Our investigation into one of our antibody‐expressing cell lines, mAb1 CHO DG44, revealed that transcriptional downregulation, and hence lower expression of PDGFRa protein, was the likely cause of poor growth outcomes during production when the cells were sourced from seed train cultures exposed to low pH (Figure 1a,b). Previously we have shown that this poor growth outcome correlated with increased intracellular BiP levels, which is indicative of UPR activation 16 . When the UPR was chemically induced, PDGFRa protein levels also decreased due to transcriptional downregulation, a phenomenon that could be reversed by chemical inhibition of the PERK branch of the UPR pathway, suggesting that PERK activation mediates PDGFRa downregulation (Figures 1c–f and S1a–c).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Our investigation into one of our antibody‐expressing cell lines, mAb1 CHO DG44, revealed that transcriptional downregulation, and hence lower expression of PDGFRa protein, was the likely cause of poor growth outcomes during production when the cells were sourced from seed train cultures exposed to low pH (Figure 1a,b). Previously we have shown that this poor growth outcome correlated with increased intracellular BiP levels, which is indicative of UPR activation 16 . When the UPR was chemically induced, PDGFRa protein levels also decreased due to transcriptional downregulation, a phenomenon that could be reversed by chemical inhibition of the PERK branch of the UPR pathway, suggesting that PERK activation mediates PDGFRa downregulation (Figures 1c–f and S1a–c).…”
Section: Discussionmentioning
confidence: 68%
“…Previously we have shown that this poor growth outcome correlated with increased intracellular BiP levels, which is indicative of UPR activation. 16 When the UPR was chemically induced, PDGFRa protein levels also decreased due to transcriptional downregulation, a phenomenon that could be reversed by chemical inhibition of the PERK branch of the UPR pathway, suggesting that PERK activation mediates PDGFRa downregulation (Figures 1c-f and S1a-c). This was further confirmed when chemical induction of UPR in a PERK KO cell line did not result in downregulation of PDGFRa expression (Figure 1g).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The data also reveals cells to be oxidatively stressed at the high density, thus giving indications for possible optimization strategies for such processes. Tung et al then present data on slight variations in pH during the seed train of an industrial scale process, which results in increased changes in the BiP concentration, thus revealing problems associated with proper protein folding und ER related stress under these conditions. While other standard process parameters such as growth and productivity were not obviously affected, such stress‐situations can still impact on the final process performance.…”
mentioning
confidence: 99%